1970
DOI: 10.1039/an9709500402
|View full text |Cite
|
Sign up to set email alerts
|

A method for the determination of aromatic isocyanates in air in the presence of primary aromatic amines

Abstract: A method is described for the determination of aromatic isocyanates in air in the presence of primary aromatic amines. Samples of the test atmosphere are drawn simultaneously through two different absorbing solutions a t 1 1 minute-1 for 10 minutes. One sample is collected in a dimethylformamide solution of 1,6-diaminohexane and the other in a dimethylformamidehydrochloric acid solution of 1,6-diarninohexane. The aromatic amine present, or produced, in each absorbing solution is diazotised and coupled with N-(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1982
1982
2000
2000

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Standard atmospheres of PAPI were produced as aerosols ® Based on a 45-L air sample. Value was determined by colorimetric impinger method used for corroboration (7). 6 Average of six samples.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Standard atmospheres of PAPI were produced as aerosols ® Based on a 45-L air sample. Value was determined by colorimetric impinger method used for corroboration (7). 6 Average of six samples.…”
Section: Resultsmentioning
confidence: 99%
“…Miskovich has shown that trace level NMP can be quickly and accurately determined by dissolving extracts or raffinates in hydrocarbon solvents and analyzing the solutions by gas chromatography using a nitrogen-phosphorus detector (NPD) (7). However, after several analyses, detector response from the elution of the high molecular weight hydrocarbons forces purging the column at elevated temperatures for several hours to remove these hydrocarbons and stabilize the background interference.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The air containing TDI vapour was led into the exposure chamber after dilution with clean, dry air to achieve appropriate at mospheric concentrations. The concentration of TDI in the atmos phere was determined by Marcali's method as modified by Meddle and Wood [1970], Air from the chamber was drawn through two sintered glass bubblers in series containing an acid-absorbing solu tion in which the TDI was hydrolysed to the amine. The amine was subsequently diazotised and coupled to form a coloured complex, the intensity of which is a measure of the concentration of the TDI originally present in the air.…”
Section: Atmosphere Generation and Analysismentioning
confidence: 99%